Anthropic Ideology Throughout the Ages - Heller, Michael (Theoria et Historia Scientiarum, 2007)
The goal of the present study is to try to understand this phenomenon. A working hypothesis is that man always looked for his place in the Universe and that the anthropic principles provide him new guide-lines in his struggle to find a meaning of his existence. To verify this hypothesis, or to make it more precise, would require a thorough study in the style of the „history of ideas”. The present paper should be regarded as a first reconnaissance along this way. I shall focus on the „extraterrestrial life debate” which has obvious ideological connections with tendencies giving force to the anthropic principles, and on philosophical implications of the Copernican revolution which spoiled man his cosmologically central position. Because of the richness of the available historical material, my discussion becomes more sketchy as it enters the after Galileo and Newton period of the modern sciences. All this makes of my conclusions only provisional suggestions pawing the way (let us hope) for better documented results. Composition of the paper reflects the main epochs of the development of the Western philosophy and science.